2017
DOI: 10.18178/joaat.4.4.372-375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Doses of Vermicompost Applications on P and K Contents of Pepper (Capsicum annuum L.) and Eggplant (Solanum melongena L.)

Abstract: In this study, which was carried on in controlled circumstances, the effects of the increasing doses of vermicompost implementation [0 (VC1), 3 (VC2), 5 (VC3), 7(VC4), %] on the P and K contents of pepper (capsicum annuum L.) and eggplant (solanum melongena L.) have been investigated. When P and K analysis results of pepper and eggplants analyzed were observed, it has been realized that there is a linear increase in both element values with vermicompost applied at increasing rates. While the phosphorus and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Furthermore they improve soil aeration, this might explain the consistent increase in fruit number, fruit weight and fruit length by application of vermicast and vermitea. Vermitea can be economically, productivity suitable for healthy plant growth, increased the fruit quality, yield and for enhancement the soil environment (Gandhi and Sundari, 2012;Sundararasu and Jeyasankar, 2014and Belliturk et al, 2017and Soraya et al, 2020.These reported that, significant increases in growth and yield of treated plants with vermitea, due to high available amounts of macro and micro-elements in vermitea. Positive effect of vermicompost at 5t/ha either or combination with FYM or chemical fertilizers lead to enhance the vegetation, flowering, fruiting stage, total yield and food quality of eggplants (Seethalakshmi,2011and Chaulagain et al,2017and Bellitürk, 2018.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore they improve soil aeration, this might explain the consistent increase in fruit number, fruit weight and fruit length by application of vermicast and vermitea. Vermitea can be economically, productivity suitable for healthy plant growth, increased the fruit quality, yield and for enhancement the soil environment (Gandhi and Sundari, 2012;Sundararasu and Jeyasankar, 2014and Belliturk et al, 2017and Soraya et al, 2020.These reported that, significant increases in growth and yield of treated plants with vermitea, due to high available amounts of macro and micro-elements in vermitea. Positive effect of vermicompost at 5t/ha either or combination with FYM or chemical fertilizers lead to enhance the vegetation, flowering, fruiting stage, total yield and food quality of eggplants (Seethalakshmi,2011and Chaulagain et al,2017and Bellitürk, 2018.…”
Section: Resultsmentioning
confidence: 98%
“…It is an economically important crop in Africa and also cultivated in warm temperate regions of the Mediterranean. Eggplant fruits riche of minerals (K, Mn, Fe and Ca), vitamins for human health and it is low in calories, not only is used as cooking vegetable but also it has many medical values; which is help to lower the blood cholesterol levels, regulate high blood pressure and suitable for diet and diabetic (Gandhi and Sundari, 2012, Belliturk et al, 2017and Al Ali et al, 2019. Vermicompost is riches with macro (N, P and K), micro (Fe, Mn, Mg, Zn) nutrients, beneficial soil microbes; e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is well known that chemical fertilizers are playing vital role for higher agricultural production. In Turkey, both production and use of this fertilizer are increasing day by day (Bellitürk et al, 2017b;Bellitürk, 2018). However, in the present scenario the overuse of fertilizers is posing environmental problems which are often difficult to overcome in developing countries (Sutton et al, 2011;Sun et al, 2012;Bellitürk, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing cost of chemical fertilizers has prompted farmers in Turkey to rethink their soil fertility practices. New, improved practices will include vermicompost (Bellitürk et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%